(untitled) (Marketing Journal, 2025)
This study assessed the impact of eco -digital marketing strategies on the export competitiveness of grape -producing small and medium -sized enterprises (SMEs) in Uzbekistan. Using regression and correlation models, a statistically significant № 10-SON OKTA BR, 2025 -YIL 531 relationship was identified between digital variables —such as artificial intelligence adoption, green certification, digital traceability, and interactive campaign coverage — and the export performance index. Empirical data were collected through field obser vations and semi -structured interviews with stakeholders. Based on the findings, a transformative model was proposed to support sustainability and enhance investment attractiveness in the viticulture sector.